Clinical evidence and GRADE assessment for breviscapine injection (DengZhanHuaSu) in patients with acute cerebral infarction. (15th November 2020) - Lyu, Jian; Xie, Yanming; Sun, Menghua; Zhang, Lidan
Abstract: Ethnopharmacological relevance: Breviscapine injections (DengZhanHuaSu, DZHS) is a famous Chinese patent medicine authorized by China Food and Drug Administration, which is widely used to treat acute cerebral infarction (ACI) in China. Aim of the study: In the present study, meta-analysis has been performed in determining the efficacy and safety of DZHS combined with conventional treatment (CT) for ACI and GRADE assessment. Materials and methods: Randomized controlled trials (RCTs) testing the use of DZHS for treating ACI were screened by searching the databases of the Cochrane Library, PubMed, Embase, and Web of Science as well as four Chinese databases. Meta-analysis was carried out with RevMan 5.3 and Stata 16.0 software. The quality of research evidence was assessed by the GRADEprofiler (GRADEpro version: 3.6). Results: Forty-three studies (n = 4618) were included. When compared to the control groups, the total effective rate of the national institutes of health stroke scale (NIHSS) was higher in the experimental group with DZHS (RR = 1.23, 95% CI = 1.19 to 1.28, P  < 0.001; RR = 1.29, 95% CI = 1.21 to 1.38, P  < 0.001); clinical symptoms and signs were improved in the experimental group with DZHS (RR = 1.17, 95% CI = 1.10 to 1.24, P  < 0.001; RR = 1.25, 95% CI = 1.11 to 1.42, P  < 0.001); the incidence of adverse reactions was reduced in the experimental group with DZHS (RR = 0.50, 95% CI = 0.26 to 0.98, P  = 0.044); and the NIHSS score was decreased in the experimental group with DZHS (WMD = −3.30, 95% CI = −3.86 to −2.73, P  < 0.001). Conclusions: DZHS combined with CT is conditionally recommended to improve the total effective rate of the NIHSS, clinical symptoms, and neurological deficits and reduce the incidence of adverse reactions, and no serious adverse reactions were noted. The GRADE assessment indicates that the overall certainty quality of evidence is low. Further large-scale, well-designed and high-quality RCTs are needed to confirm the positive results. PROSPERO registration No. CRD42019128856. Graphical abstract: Image 1